An algebra problem by A Former Brilliant Member

Algebra Level 1

If a x b x = a 2 b 2 \frac{a-x}{b-x}=\frac{a^2}{b^2} , then value of x x is?

b a + b \frac{b}{a+b} a 2 a + b \frac{a^2}{a+b} a b a + b \frac{ab}{a+b} a a b \frac{a}{a-b}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Nikhil Raj
May 31, 2017

Given , a x b x = a 2 b 2 ( a x ) b 2 = ( b x ) a 2 a b 2 b 2 x = a 2 b a 2 x a 2 x b 2 x = a 2 b a b 2 x ( a 2 b 2 ) = a b ( a b ) x = a b ( a b ) ( a b ) ( a + b ) x = a b a + b \dfrac{a - x}{b - x} = \dfrac{a^2}{b^2} \\ \implies (a - x)b^2 = (b - x)a^2 \\ \implies ab^2 - b^2x = a^2b - a^2x \\ \implies a^2x -b^2x = a^2b -ab^2 \\ \implies x(a^2 - b^2) = ab(a - b) \\ \implies x = \dfrac{ab(a - b)}{(a - b)(a + b)} \\ \therefore x = \boxed{\dfrac{ab}{a + b}}

a x b x = a 2 b 2 \dfrac{a-x}{b-x}=\dfrac{a^2}{b^2} \implies cross-multiplying, we get

a b 2 x b 2 = b a 2 x a 2 ab^2-xb^2=ba^2-xa^2

then,

x a 2 x b 2 = b a 2 a b 2 xa^2-xb^2=ba^2-ab^2

then,

x ( a 2 b 2 ) = b a 2 a b 2 x(a^2-b^2)=ba^2-ab^2 \implies dividing both sides by a 2 b 2 a^2-b^2 , we get

x = b a 2 a b 2 a 2 b 2 x=\dfrac{ba^2-ab^2}{a^2-b^2}

then,

x = a b ( a b ) ( a b ) ( a + b ) = a b a + b x=\dfrac{ab(a-b)}{(a-b)(a+b)}=\boxed{\dfrac{ab}{a+b}}

Diana Rivache
Nov 10, 2015

Given the equality in the problem, we have (a-x)b^2 = (b-x)a^2 Then, (a)(b^2) - (x)(b^2) = (b)(a^2) - (x)(a^2) Then we reorganize the equation to get (a)(b^2) - (b)(a^2) = (x)(b^2) - (x)(a^2) Factoring x in the right side and ab in the left side we have (ab)(b - a) = (x)(b^2 - a^2) Then we clear x by dividing so we get (ab)(b - a) / (b + a)(b - a) = x Simplify (b - a) and we finally get x = (ab) / (a+b)

1 pending report

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...